Hope Harbor - Book 1 - Hannon, Irene (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2015)
"Tracy Campbell never wanted to leave Hope Harbor, Oregon, or the idyllic three-generation cranberry farm where she grew up. But life--and love--altered her plans. When tragedy strikes and changes her plans yet again, she finds herself back in her hometown with a floundering farm to run and a heartbreaking secret. Romance is not on her agenda. Nor is it on Michael Hunter's. The visitor from Chicago has daunting secrets of his own. But when Tracy recruits him to help save a struggling charitable organization, the winds of change begin to sweep through Hope Harbor, bringing healing, hope, and love to countless lives--including their own"--Amazon.com.
Keywords: Farm life -- Fiction; Homecoming -- Fiction; Man-woman relationships -- Fiction; Oregon -- Fiction; Love stories; Christian fiction